Inventário da oferta turística de Cerro Corá - Edição 2024 - Taveira, Marcelo da Silva (Org.) (2024)
The municipality of Cerro Corá is located in the Central Potiguar Mesoregion and in the Serra de Sant'Ana Microregion, 190 km from Natal, capital of the State of Rio Grande do Norte, and is part of the Brazilian Tourism Map and the Tourist Governance Instance. Seridó. Cerro Corá has significant tourist potential to be developed, as it is located in the Serra de Sant'Ana, the coldest portion of the Seridó region, making the municipality stand out for its mountain climate and elements of significant geo-environmental diversity and unique attractions. natural tourism with significant regional differences. Furthermore, the municipality is part of the UNESCO World Geopark Seridó, featuring four geosites of great geological value, namely the geosites, Cruzeiro de Cerro Corá, Source of the Potengi River, Serra Verde and Vale Volcanico. These factors make Cerro Corá a destination with great latency for ecotourism and adventure tourism. The Tourist Inventory is the first methodological and technical phase in the field of tourism planning and regional development, to assist municipal public management and entrepreneurs in the productive sector in the elaboration of policies and strategic actions, as well as in decision-making and directing resources and investments, based on real and scientifically verified information and proven through theories and research techniques. The inventory of the tourist offer in the municipality of Cerro Corá will contribute to improving management and the design and format of sustainable, creative and innovative tourist products.